Practice variation in induction of labour: women’s role in the decision-making process - Brabers, Anne E. M.; Haaren–Ten Haken, Tamar M. Van; Keulen, Judit K. J.; Offerhaus, Pien M.; Nieuwenhuijze, Marianne J.; de Jong, Judith D. (Research in Health Services & Regions, 2025)
In the Netherlands, percentages of induction of labour (IOL) range from 14.3 to 41.1% in regional maternity care networks (MCNs). In this study, we focus on women’s contribution in explaining this variation in range. We examine if different factors at the level of the individual woman (micro) and the level of the woman’s social context (meso) are related to decision-making on IOL, and the variation. We used an online questionnaire inviting women counselled for IOL ( n = 180, response rate 40%) from six different MCNs, three with a high and three with a low percentage of IOL. Factors included are, for example, attitude towards birth, reason for IOL, and social norms. Descriptive statistics and regression analyses were performed to examine the relation between the included factors and the intended decision on IOL. Our results show that only the factor women’s attitude towards birth is related to the intended decision on IOL. The more women believe that birth is a medical process, the higher the odds that the intended decision is to induce labour. This may contribute to variation in IOL between individual women, but appears to contribute less to variation in IOL between MCNs. This is because the percentages of women with an intended decision for IOL do not differ within MCNs with a low or high percentage of IOL. A next step in explaining practice variation, is to examine mechanisms at the level of the individual healthcare provider (micro) and the MCN (meso).